Deconstructing Saudi Arabia’s Foreign Aid Motives to Yemen - Andrini, Ghita Fadhila; Hidayat, Taufik; Yulianti, Dina (Global: Jurnal Politik Internasional, 2022)
This research assesses the motives of Saudi Arabia’s aid to Yemen. Saudi Arabia has been the most significant donor to the country whilst threatening humanitarian conditions in Yemen through its military intervention. Thus, this research aims to unveil the Kingdom’s reasons to provide foreign aid to Yemen whilst doing the military intervention. This research uses the seven foreign aid frames according to Veen (2011) to analyse possible interest implied in the Kingdom’s foreign aid delivery to Yemen. The method used in this research is a literature review by analysing the Kingdom’s official statements published on the government's official websites and an interview with a Middle East expert. The statements were coded using qualitative analysis software, Atlas.ti. This study finds that Saudi Arabia has four significant motives to provide foreign aid to Yemen, namely humanitarian, reputation, security, and power. The four frames are connected but mostly related to the Kingdom’s objective to maintain its power. Thus, foreign aid is used as a soft power tool to preserve Saudi Arabia’s influence against economic and security threats, prevent an unfriendly regime from ruling Yemen, and increase its reputation in the international sphere.